Radiation-Induced Erectile Dysfunction in Prostate Cancer Patients: Up-to-Date View on Pathogenesis - R. V. Novikov; S. N. Novikov; V. V. Protoshchak; I. B. Dzhalilov; S. S. Litinskiy (Вестник рентгенологии и радиологии)
The true causes of sexual disorders after radiation treatment of prostate cancer, among which the central role is occupied by erectile dysfunction, are still not fully clarified. The number of patients who undergo various radiation-exposure options as a radical therapy is steadily increasing, which makes the issue very relevant. This literature review provides up-to-date data on the most studied probable mechanisms of the erectile function status decline after radiation therapy for prostate cancer.